TANGGUNG JAWAB PENGEMBANG PERUMAHAN DALAM PENYERAHAN FASILITAS UMUM DAN FASILITAS SOSIAL KEPADA PEMERINTAH DAERAH - Mutiara Tasya Febrinia (2022)
Public facilities and social facilities submission of a residential area is the responsibility of the housing developer. However, there are still many housing developers who do not or have not submitted the public facilities to the Local Government. The government made various regulations regarding public facilities and social facilities to maintain the implementation of procurement, delivery, and management of public facilities and social facilities or infrastructure, public facilities and utilities (PSU) running in an orderly manner and prevent problems related to procurement, delivery, and management PSU. During the research, we found that there are still many cases related to Housing Developers who do not submit public facilities to the Local Government, one of them was occurred in Ruko 1000, Cengkareng, West Jakarta. In this study, the research method used is normative legal research. Based on the research results, the developer's responsibility for the submission of public and social facilities in the housing that they built is an obligation because if the facility submission is not carried out properly, it will harm many parties. Sanctions that can be imposed on Developers who do not submit public and social facilities are contained in Article 150 and Article 151 of Law no. 1 of 2011 concerning Housing and settlements. Keyword: Facilities Submission, Developer, Housing, Law